Critique of journalistic reason philosophy and the time of the newspaper - Vandeputte, Tom 1983- (Fordham University Press, 2020)
This book examines philosophy's recurrent preoccupation with journalism. It shows how modern European philosophy's preoccupation with the news inflects theories of history, time, and language
Keywords: Philosophie; Presse